RESPONS PERTUMBUHAN DAN HASIL TANAMAN SELEDRI (APIUM GRAVEOLENS L.) TERHADAP MEDIA TANAM DAN KONSENTRASI LARUTAN NUTRISI YANG BERBEDA PADA WICK SYSTEM - Maria Ulfa; Hadi Pranoto; Susylowati Susylowati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
This research aims to find out 1) the interaction between the medium of planting and the concentration of nutrient solutions to the growth and yield of celery plants hydroponically. 2) types of planting media that can give different influences on the growth and yield of celery plants, and 3) concentration of nutrient solution that provides the best growth and yield of celery plants in different planting media.The research was conducted from December 2019 to February 2020 at the Integrated Laboratory of the Faculty of Agriculture of Mulawarman University, Samarinda. The research used factorial exsperiment 3×4 on Randomized Completely Block Design (RCBD), replicated three times with each treatment consisting of three plants. The first factor is the planting medium consisting of rockwool, charcoal husk, and combination of charcoal husk + tea amps. The second factor is the concentration of AB Mix nutrient solution consists of 500, 1,000, 1,500, and 2,000 ppm. The data was analyzed with test F and continued Least Significant Difference (LSD) test with a level of 5%. The results showed that there is an interaction between planting media and concentration of nutrient solution in the growth and yield of celery plants. The interaction between the combination of charcoal planting media + tea pulp and concentration of 1,500 ppm is not real with the interaction of rockwool planting media and concentration of 1,500 ppm. From various types of planting media used, charcoal husk planting media provides the best influence on the growth and yield of celery plants. Based on polynomial orthogonal test the concentration of nutrient solution with an optimum point of 1,460.84 ppm affects the growth and yield of celery plants with a maximum dry weight of 2.14 g.